Denitrification in intertidal sediments of a tropical estuary subject to increasing development pressures - Julia Fortune; Mirjam Kaestli; Edward C. V. Butler; Karen Gibb (Aquatic Sciences, 2022)
Darwin Harbour is a working port and the most populated city in the Northern Territory of Australia. This macrotidal estuary is located in the wet–dry tropics of Northern Australia and notwithstanding mounting development pressures in the region, is largely unmodified. The prevailing oligotrophic condition of estuarine waters suggest that biogeochemical cycling in sediments remain active, buffering the influence of anthropogenic inputs. We tested the hypothesis that nutrient hotspots exist in depositional low-velocity zones, with a gradient of high to low nitrogen processing from the upper to outer reaches of the estuary. A number of factors were examined for their influence on the effectiveness of denitrification in these depositional zones, a putative key process driving nitrogen removal, with particular emphasis on carbon-loading extremes in tidal creeks, spatial gradients along the estuary and the influence of seasonality. There were significant differences in process rates between hypereutrophic/eutrophic tidal creeks that receive the largest proportion of treated sewage loads in the region and the mesotrophic/oligotrophic tidal creeks that were comparatively undisturbed. Net benthic nutrient fluxes and dinitrogen efflux rates were more than an order of magnitude higher and lower, respectively, in degraded (hypereutrophic/eutrophic) tidal creek systems where denitrification efficiency (DE%) was −2 day −1 ) and denitrification efficiency remained > 65%, particularly during the wet season. On a whole-of-estuary basis, denitrification in conjunction with mechanisms such as burial could feasibly make a substantial impact, abating the influence of anthropogenic inputs. Although considerable variability was encountered, particularly across seasons, the hypothesis of elevated denitrification rates as nutrient hotspots in depositional zones along the estuary was not convincing. More influential are tidal creeks as potential ‘reactors’ for N cycling and removal, but their capacity can be degraded by overloading with nutrients.

The emergence of marine recreational drone fishing: Regional trends and emerging concerns - Alexander C. Winkler; Edward C. Butler; Colin G. Attwood; Bruce Q. Mann; Warren M. Potts (Ambio, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Evidence for protandry in Polydactylus quadrifilis in the Kwanza Estuary, Angola, and its implications for local fisheries - Edward C. Butler; Amber-Robyn Childs; Alexander C. Winkler; Marianne V. Milner; Warren M. Potts (Environmental Biology of Fishes, 2018)

Recent environmental change and trace metal pollution in World Heritage Bathurst Harbour, southwest Tasmania, Australia - Krystyna M. Saunders; Jennifer J. Harrison; Edward C. V. Butler; Dominic A. Hodgson; Andrew McMinn (Journal of Paleolimnology, 2013)

(2-Methoxyethoxy)acetic acid: a urinary biomarker of exposure for jet fuel JP-8 - Clayton B’Hymer; Patricia Mathias; Edward Krieg; Kenneth L. Cheever; Christine A. Toennis; John C. Clark; James S. Kesner; Roger L. Gibson; Mary Ann Butler (International Archives of Occupational and Environmental Health, 2012)

Mercury in the marine food chain in the Southern Ocean at Macquarie Island: an analysis of a top predator, Patagonian toothfish ( Dissostichus eleginoides ) and a mid-trophic species, the warty squid ( Moroteuthis ingens ) - Tertia McArthur; Edward C. V. Butler; George D. Jackson (Polar Biology, 2003)